The orosomucoid 1 protein (α1 acid glycoprotein) is overexpressed in odontogenic myxoma - García-Muñoz Alejandro; Rodríguez Mario A; Bologna-Molina Ronell; Cázares-Raga Febe E; Hernández-Hernández Fidel C; Farfán-Morales J; Trujillo Juan J; Licéaga-Escalera Carlos; Mendoza-Hernández Guillermo (Proteome Science, 2012)
Abstract Background Odontogenic myxoma (OM) is a benign, but locally invasive, neoplasm occurring in the jaws. However, the molecules implicated in its development are unknown. OM as well as Dental Follicle (DF), an odontogenic tissue surrounding the enamel organ, is derived from ectomesenchymal/mesencyhmal elements. To identify some protein that could participate in the development of this neoplasm, total proteins from OM were separated by two-dimensional electrophoresis and the profiles were compared with those obtained from DF, used as a control. Results We identified eight proteins with differential expression; two of them were downregulated and six upregulated in OM. A spot consistently overexpressed in odontogenic myxoma, with a molecular weight of 44-kDa and a pI of 3.5 was identified as the orosomucoid 1 protein. Western blot experiments confirmed the overexpression of this protein in odontogenic myxoma and immunohistochemical assays showed that this protein was mainly located in the cytoplasm of stellate and spindle-shaped cells of this neoplasm. Conclusion Orosomucoid 1, which belongs to a group of acute-phase proteins, may play a role in the modulation of the immune system and possibly it influences the development of OM.